Counselling and pregnancy outcomes in women with congenital heart disease- current status and gap analysis from Madras Medical College Pregnancy And Cardiac disease (M-PAC) registry - Justin Paul Gnanaraj (Elsevier, 2021)
Introduction: Congenital heart disease (CHD) is becoming an increasingly important cause of heart disease in pregnancy in low- and middle - income countries (LMICs). Preconception and contraception counselling based on risk stratification has the potential to reduce maternal complications. Data is lacking from LMICs on the availability and effectiveness of preconception counselling (PCC) in women with CHD (WWCHD). Methods: Madras Medical College Pregnancy and Cardiac disease (M-PAC) Registry is a single center prospective observational registry conducted at a tertiary referral institution in South India from July 2016 to December 2019. Baseline features and feto-maternal outcomes were compared in WWCHD with and without PCC. Predictors of post-delivery contraception were identified. Results: Of the 107 eligible pregnancies with data on counselling, only 49.5% had received PCC. Pregnancies involving women with corrected CHDs (62.3% vs 33.3%; P ​= ​0.006) and cyanotic CHD (20.8% vs 11.1%; P ​= ​0.042) were more likely to get PCC. High risk mWHO categories were non-significantly less likely to get PCC (32% vs 39%). Primary outcome of death or heart failure was non-significantly low in the PCC group (3.8% vs 7.4% P ​= ​0.4). Patients with high risk m WHO categories were less likely to get Tier I contraceptives post-delivery (46% vs 79.7% P ​= ​0.004). Conclusion: Preconception and post conception counselling, which have the potential to improve outcome in WWCHD, are being underused in LMICs. Health care systems should ensure multidisciplinary pregnancy and heart team approach to offer timely lesion specific pre-conceptional counselling, shared decision making and appropriate peri-pregnancy care for WWCHD.